Koperasi Angkatan Tentera Malaysia Berhad / Norazrin Amin - Amin, Norazrin (Universiti Teknologi MARA, Sarawak, 2016)
Koperasi Angkatan Tentera Malaysia Berhad, or known as Koperasi Tentera was established in 1960 as a cooperative thrift and borrowing (thrift and loan). In 1975, Koperasi Tentera has converted to a multi-purpose cooperative until today. Koperasi Tentera's main objective is to improve the socio-economic status and welfare of military personnel. Membership is open to all military personnel and civil servants who work for the Ministry of Defence. As at 31 August 2015, the number and has reached 153,115 with a total of RM 1.144 billion of share capital and accumulated fees contributed by the member. The principal activity of Koperasi Tentera is on financial product such as Sharia Financing Scheme and Group Takaful Scheme. Koperasi Tentera is also involved with selected investment activities with 30 % shareholding each in the Great Eastern Takaful Malaysia Berhad and Pacific Mutual Fund Berhad.